Persepsi Perawat Manager tentang Pelaksanaan Audit Mutu Keperawatan di Ruang Rawat Inap - Indah Mulyani; Setiawan Setiawan; Bustami Syam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to explore nurse managers' perceptions about the implementation of Nursing Quality Audit in the inpatient room of RSUD Dr. H. Yuliddin Away. The method used is qualitative with a phenomenological approach. The participants in this study were 15 nurse managers. Data was collected through Focus Group Discussion (FGD) and analyzed using content analysis. The results showed that there were five themes related to the nurse manager's perception of the implementation of a quality audit of nursing in the inpatient ward, namely: 1) the meaning of audit according to the nurse manager; 2) the implementation of nursing quality audits; 3) nursing quality indicators; 4) obstacles in the implementation of nursing quality audits; 5) supporting factors for audit implementation. In conclusion, the experience of nurse managers in implementing Nursing Quality Audits in hospitals is inadequate. Keywords: Nursing Audit, Quality Indicators, Service Quality Assurance, Nurse Manager